ANALISIS PENERAPAN DAN IMPLIKASI PEMBELAJARAN BAHASA ARAB BERDASARKAN PRINSIP TEORI KOGNITIF MULTIMEDIA DI AKUN SOSIAL MEDIA INSTAGRAM @ARABICWITHENES - Muiz, Abd.; Nurmuzib, Moh Arif; Purnama, Boby Bagas (Universitas Islam Negeri Mataram, 2025)
Learning Arabic through Instagram social media is one of the alternative media to present material in an interesting and contemporary way, because Instagram has feed and reels features that support multimedia-based learning, but to present material a theory is needed to support learning to be more effective. Therefore, the purpose of this study is to analyze the application and implications based on the principles of multimedia cognitive theory in learning Arabic through the @arabicwithenes Instagram account. Using a qualitative approach, while the method used is content analysis, this study analyzes how the feeds and reels features in the account apply the six main principles of multimedia cognitive theory, namely the principles of multimedia, spatial proximity, temporal proximity, coherence, modality, and redundancy. The results of this study show that most of the content has effectively applied these principles, especially in the simultaneous use of audio and visual, which then facilitates the understanding of the pronunciation and meaning of mufradat for Instagram users, especially its followers. At the same time, however, there is still some content that applies redundancy, which has the potential to increase cognitive load. The effects of applying these principles show a positive impression on their followers in terms of increasing motivation and interest as well as understanding in learning Arabic, although the intensity of improvement needs to be carried out further, especially in terms of personalizing the content so that it is more relevant to the skill level of each individual Instagram user and follower.